Nomeação em crianças pequenas - Aniceto, Gabriela (2022)
The gap left by Skinner's lack of analysis of listener behavior in 1957 led researchers to study listener behavior, its development and its role in verbal behavior. Considering the role of listener as a requirement for the acquisition and maintenance of speaker behavior, it seems essential to study listener behavior as a condition to explain verbal behavior. Therefore, this thesis was divided into two studies. Study 1 was a conceptual work whose objectives were i) to map and characterize the Theory of Naming, analyzing its developments in relation to its conceptual and empirical aspects and its theoretical and empirical limitations and ii) to present and discuss the advances brought in the Theory of Development of Verbal Behavior, in relation to the Theory of Naming. Study 2 was a case study of a 27-month-old child at risk for language development according to the Denver II Developmental Screening Test. The participant was exposed to a teaching procedure structured in MEI with the objective of verifying the emission of the echoing behavior and of selecting for the emergence of naming, relating the child's performance in the teaching procedure with the data collected by the Denver II Test. It is concluded that future studies can use verbal landmarks and their prerequisites to identify the behaviors installed in the children's repertoire and, thus, from this point onwards to the proposition of child development programs that aim at the teaching/emergence of naming. . In addition, future empirical studies can verify the behaviors of imitation and generalized imitation before exposing children to the structured teaching procedure in MEI, so that the operants in rotation are in accordance with the skills already identified and to be taught for emergence of appointment.